ACTUALIZATION OF STYLE FEATURES OF HISTORICAL STYLES IN FORMING IMAGES OF MODERN PUBLIC SPACES ON THE EXAMPLE OF EXERCISES-IMPROVISATIONS OF STUDENTS - FUTURE ARCHITECTS - Тюрікова, Олена; Оржешко, Вадим; Нестеренко, Діана (SWorldJournal, 2025)
This study explores the reinterpretation of historical stylistic elements in the design of contemporary public spaces. The research highlights the discrepancies between societal practices and architectural design, as well as the divergence between consum